Analisis Ketahanan Pangan Rumahtangga Peserta Program Desa Mandiri Pangan di Desa Sei Geringging Kecamatan Kampar Kiri Kabupaten Kampar - Tiur Lamria Br Sitinjak; Rosnita '; Ahmad Rifai (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The purpose of this study is to analyse household food security over village food resilience Programme Participants at Sei Geringging Village in Left Kampar District of Kampar Regency. Sampling using purposive sampling method (75 people) with 30 people respondents. The result shows that the availability of food at Sei Geringging Village in Left Kampar District Kampar Regency in 2013 as village food resilience disable to provide food for villager because from eight kinds of comestible, threre are just side dish, vegetables and fruits available from the village. Total distribution of respondent income is IDR 66.339.750,00 which are 75,77% main income and 24,33% other income. The average of respondents expends is IDR 749.028,00 in which 78,88% for food expenditure and 21,12% for non food expenditure. Aspect of food consumption indicate that people have a good knowledge for food and nutrition at score of 3,70 (knowing category), in practicing prefer to fill the food needs without taking seriously for nutrients and energy standards that must be filled every day instead. That is illustrated by the number of calorie 1.197,57 Kkal which is far below from Food and Nutrients National Widya Karya Standard (2.000 Kkal and at 42,48% lower than rular calorie consumption in Riau Province. Keywords : village food resilience, food availability, food distribution and food consumption